C2B Coordination and Optimization Strategy of Enterprise Supply Chain for Internet of Things E-Commerce Management - Jing Yi; Xiao Zeng (My University, 2025)
With the development of economy and the improvement of consumption level, consumers' demand for product style, quality and price is also increasing. The traditional e-commerce model has been unable to meet the personalized needs of users. The Customer to Business (C2B) model is an e-commerce model based on customer' needs, and enterprises can respond quickly. The main purpose of this paper is to discuss how to use the Internet of Things (IoT) technology to analyze and study the C2B supply chain of e-commerce, as well as the strategy of collaborative optimization. For C2B supply chain of e-commerce enterprises (e-CEs), this paper considered the impact of many factors on supply chain pricing, such as Degree of Effort for Personalized Customization (DEPC) r and the impact coefficient of cross price ϕ, which provided a theoretical basis for optimizing pricing decisions.
Keywords: Supply chain optimization; E-commerce and Technology Innovations